Antimicrobial resistance E. coli, Staphylococcus and Salmonella Hatirjheel lake and Buriganga river: a threat to water quality and public health - Anchol, Lamia Zafor; Adhikari, Progga; Hossain, Zarin; Mif, Nawshin Islam; Natasha, Tahaba Nasrin; Mondal, Bristy (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2024.